2011
DOI: 10.1038/sj.bjc.6606064
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive androstane receptor agonist CITCO inhibits growth and expansion of brain tumour stem cells

Abstract: Background:Brain tumours present unique challenges to conventional therapies and pose major health problems around the world. Brain tumour stem cells (BTSCs) represent a small fraction of tumour cells that maintain growth, drug resistance and recurrence properties. Constitutive androstane receptor (CAR) is a nuclear receptor transcription factor that regulates drug metabolism and homoeostasis. In this study, we examined the effect of CAR agonist, 6-(4-chlorophenyl)imidazo[2,1-b][1,3]thiazole-5-carbaldehydeO-(3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 41 publications
2
45
0
Order By: Relevance
“…The mRNA of CAR is highly expressed in human liver and kidneys but is weakly expressed or not expressed at all in various other tissues [115,117]. Recent reports also indicate that CAR is expressed at varying levels in some non-small cell lung cancer and brain cancer stem cells, but the mechanism of action does not appear to involve members of the CYP family [118,119]. …”
Section: Expression and Enzymatic Activities Of Cyp3a4 And Cyp3a5mentioning
confidence: 99%
“…The mRNA of CAR is highly expressed in human liver and kidneys but is weakly expressed or not expressed at all in various other tissues [115,117]. Recent reports also indicate that CAR is expressed at varying levels in some non-small cell lung cancer and brain cancer stem cells, but the mechanism of action does not appear to involve members of the CYP family [118,119]. …”
Section: Expression and Enzymatic Activities Of Cyp3a4 And Cyp3a5mentioning
confidence: 99%
“…Besides ubiquitous expression in normal tissues, Rfc is expressed in various human tumor cell lines including leukemic blasts [2]. Moreover, expression of nuclear receptor CAR was shown in various human cancer cells including brain tumor stem cells [58] and hepatoma or colon carcinoma cells [59]. Concerning the clinical relevance for patients with ALL receiving MTX and PB, recent studies demonstrated expression of CAR in human peripheral blood mononuclear cells [60] as well as expression and inducibility of CYP 2B6 by PB-type CYP450 inducers in the human leukemia HL-60 cell line [61].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a recent study showed that CAR is a positive regulator of MDR1 (Pgp), MRP2 and BCRP expression in rat and mouse brain capillaries (Wang, B. et al, 2010). Moreover, another study demonstrated that CITCO inhibits the growth and expansion of brain tumor cancer stem cells by inducing cell cycle arrest and apoptosis in vitro (Chakraborty et al, 2011). Although the CAR-mediated antineoplastic effect is not known, these results support the use of CAR agonists as a new therapy to target brain tumor cancer stem cells for the treatment of glioma.…”
Section: Pxr and Carmentioning
confidence: 99%